A survey of social media use in emergency situations: A literature review. (June 2021) - Abdulhamid, Najeeb Gambo; Ayoung, Daniel Azerikatoa; Kashefi, Armin; Sigweni, Boyce
This study reviews literature on the use of Social Media (SM) in emergency response operations while identifying gaps in this research stream that need attention from Information Systems (IS) researchers. The research is grounded in past works and attempts to build on research on the application of SM in emergencies. It focuses on understanding the role of SM in the prevention, management and response to emergencies. The review contains a detailed literature exposition of IS and disasters journals. The appraisal of such research stream led the review to focus on the concept of digital volunteerism as an offshoot of crowdsourcing initiatives. Findings from the review reveal that previous studies overlooked the interfacing challenges between formal and traditional aid agencies on one hand and digital humanitarians on the other. Consequently, we identify gaps in the extant literature and propose areas of interest for future research.